Ball politics: João Havelange and Brazilian football, memories and biography (1958 - 1975) - Livia Gonçalves Magalhaes (Universidad Politécnica de Madrid, 2024)
The article brings as an object of reflection the study of the biography and life trajectory of João Havelange (1916-2016), more specifically the period in which he was president of the Brazilian Sports Confederation (CBD), between 1958 and 1975. His sport´s leadership in Brazil has gone through dictatorial and democratic periods, moments of developmentalist and nationalist euphoria, and confrontations of political and economic crises. At the same time, his biography is closely intertwined with the processes of institutionalization of sports practices in the country, which at many times bore the imprint of the leader, but mainly, they usually reflect issues dear to the political projects in dispute at the time. From the study of this period of his biography, it is demonstrated how a national sports management model was consolidated, marked by a developmentalist logic, in accordance with the national context. This model was exhausted with the neoliberal project from 1990. Finally, starting from the debate on the multiple memories built on and by the elites, it is shown how Havelange represents the rise and exhaustion of a model, successful for almost the entire XX century in Brazil.